2023
DOI: 10.1088/1361-6587/acc96d
|View full text |Cite
|
Sign up to set email alerts
|

Global ‘zero particle flux-driven’ gyrokinetic analysis of the density profile for a TCV plasma

Abstract: TCV is a small-sized tokamak, where finite size effects (often called ‘rho-star’ or ‘global’ effects) could significantly impact the heat and particle fluxes, leading to discrepancies between gyrokinetic flux-tube results and global ones [McMillan et al., 2010 Phys. Rev. Lett.]. The impact of global effects on the radial profile of the plasma density has been investigated in a previous study for a particular TCV discharge with negligible particle source, satisfying the ‘zero particle flux’ condition. A radiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…To conclude this section on the modelling, it has been observed that the local gyrokinetic approximation employed in these analyses with the GENE code is not sufficient to grasp the accurate dynamics of the unstable fast-ion-driven modes. Global simulations are therefore required, since firstly the turbulence structures is way much larger than the few lowest mode rational surfaces and, moreover, the non-local effects may play an important role when evaluating the global level of turbulent transport in TCV [76][77][78]. For these reasons, future efforts will be dedicated to global modelling of the here discussed TCV scenario including bulk and fast-ion transport in flux-driven gyrokinetic simulations.…”
Section: Nonlinear Local Simulations With Fast Ionsmentioning
confidence: 99%
“…To conclude this section on the modelling, it has been observed that the local gyrokinetic approximation employed in these analyses with the GENE code is not sufficient to grasp the accurate dynamics of the unstable fast-ion-driven modes. Global simulations are therefore required, since firstly the turbulence structures is way much larger than the few lowest mode rational surfaces and, moreover, the non-local effects may play an important role when evaluating the global level of turbulent transport in TCV [76][77][78]. For these reasons, future efforts will be dedicated to global modelling of the here discussed TCV scenario including bulk and fast-ion transport in flux-driven gyrokinetic simulations.…”
Section: Nonlinear Local Simulations With Fast Ionsmentioning
confidence: 99%